MBChB 5th year student response To E-Learning within orthopaedic surgery during Covid-19 - Gamieldien, Hammaad (Division of General Surgery, 2025)
Background. With the onset of the COVID-19 pandemic and the subsequent country-wide lockdown, South African (SA) universities were forced to quickly adapt to teaching that minimised or eliminated in-person contact. The pandemic period necessitated rapid changes to the way in which learning occurs and resulted in significant shifts in the academic environment. There is limited evidence in the literature to support e-learning in undergraduate orthopaedic training. This is the first study of its kind evaluating e-learning in orthopaedic surgery in a middle-to-low- income country. Objectives. To identify the University of Cape Town fifth-year MB ChB cohort's attitudes towards the e-learning component of blended learning during the COVID-19 pandemic. It also aimed to investigate whether e-learning facilitates comparable levels of confidence and results among students and face-to-face methods. Methods. Multi-year cross-sectional survey analysis was completed by retrospectively analysing the students' end-of-block evaluations and end-of-block marks. Responses from the cohorts between 2016 and 2020 were compared. Results. Regarding course definition, workload, course organisation, intended preparation and course presentation, the 2020 cohort's responses were similar to those of previous years. The 2020 cohort agreed that the e-learning material was relevant; this response was higher than in previous years. They also agreed that the online practical sessions were useful and that the course stimulated more interest. Significantly, they also strongly agreed that the online course was easier to attend and participate in than in previous years. The 2020 cohort perceived the end-of-block assessment to be somewhat unreasonable; however, this cohort yielded similar grades compared with previous cohorts. Subjectively, the students' responses to e-learning were positive, as many of them welcomed the usefulness and stimulation of online media as a study tool. Students felt that more time should be made available to work through online material and that there was incongruity between the content taught and the content of the endof-block assessments. Conclusion. Subjectively, the students' responses to e-learning were positive, as many of them welcomed the usefulness and stimulation of online media. With comparable outcomes in terms of student confidence and final marks (compared with traditional teaching only), it further encouraged a move towards formulating a novel blended learning curriculum. With these positive findings, we were able to explore the possibilities of developing an e-learning course curriculum incorporating international blended learning practices, using locally sourced SA evidence-based literature to provide orthopaedic teaching relevant to our unique setting.